A new approach to stream cipher: Unsystematic cipher - Tas, Oguzhan; Alatas, Bilal; Akın, Erhan (My University, 2004)
The encryption technique proposed in this study encrypts / decrypts in binary form. For each character in the plaintext, a randomly generated number (r), called added number, makes the cipher of the character in 2r different ways. In addition to this process, the character in the plaintext is converted into binary form and divided into parts according to the values of the added number. Different from the One Time Pad Cipher, proposed as perfect cipher in the literature, different ciphertexts are obtained from the same key. This is one of the advantages of the proposed technique. Besides, its more structural simplicity in comparison with the other stream cipher algorithms makes its development in hardware and software easy.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği